Antibacterial Activity against Clinical Strains of a Natural Polyphenolic Extract from Albariño White Grape Marc - Tamara Manso; Marta Lores; José Luis R. Rama; Rosa-Antía Villarino; Lorena G. Calvo; Aly Castillo; María Celeiro; Trinidad de Miguel (MDPI AG, 2023)
Infections caused by multidrug-resistant bacteria are becoming increasingly frequent and sometimes difficult to treat due to the limited number of antibiotics active against them. In addition, they can spread between countries and/or continents, which is a problem of great relevance worldwide. It is, therefore, urgent to find alternatives to treat infections caused by multidrug-resistant bacteria. This study aimed at exploring a possible therapeutic alternative in the fight against antibiotic resistance. Based on the known antibacterial capacity of polyphenols, we tested the antimicrobial activity of a polyphenolic extract of Albariño white grape marc on clinical strains since research on such bacteria has been very scarce until now. First, the extract was obtained using a medium-scale ambient temperature (MSAT) system, which is an efficient and sustainable extractive method. The determinations of the polyphenolic content of the extract and its antioxidant capacity showed good results. Using chromatographic and mass spectrometric tools, 13 remarkable polyphenols were detected in the extract. The antibacterial activity of our grape marc extract against nineteen clinical strain isolates, some of which are multidrug-resistant, was evaluated by means of the calculation of half of the maximum inhibitory concentration (IC50) and the value of the minimum bactericidal concentrations (MBCs). In conclusion, the extract showed effectiveness against all clinical strains tested, regardless of their level of antibiotic resistance, and shows promise in the fight against antibiotic resistance.